Hypoxic Preconditioning Promotes the Bioactivities of Mesenchymal Stem Cells via the HIF-1α-GRP78-Akt Axis - Lee, Jun Hee (Int J Mol Sci, 2017)
Mesenchymal stem cells (MSC) are ideal materials for stem cell-based therapy. As MSCs reside in hypoxic microenvironments (low oxygen tension of 1% to 7%), several studies have focused on the beneficial effects of hypoxic preconditioning on MSC survival; however, the mechanisms underlying such effects remain unclear. This study aimed to uncover the potential mechanism involving 78-kDa glucose-regulated protein (GRP78) to explain the enhanced MSC bioactivity and survival in hindlimb ischemia. Under hypoxia (2% O(2)), the expression of GRP78 was significantly increased via hypoxia-inducible factor (HIF)-1α. Hypoxia-induced GRP78 promoted the proliferation and migration potential of MSCs through the HIF-1α-GRP78-Akt signal axis. In a murine hind-limb ischemia model, hypoxic preconditioning enhanced the survival and proliferation of transplanted MSCs through suppression of the cell death signal pathway and augmentation of angiogenic cytokine secretion. These effects were regulated by GRP78. Our findings indicate that hypoxic preconditioning promotes survival, proliferation, and angiogenic cytokine secretion of MSCs via the HIF-1α-GRP78-Akt signal pathway, suggesting that hypoxia-preconditioned MSCs might provide a therapeutic strategy for MSC-based therapies and that GRP78 represents a potential target for the development of functional MSCs.